Between Jewish Tradition and Modernity : Rethinking an Old Opposition - Schmiesing, Ann (Book collections on Project MUSE., 2014)
"Although dozens of disabled characters appear in the Grimms' Children's and Household Tales, the issue of disability in their collection has remained largely unexplored by scholars. In Disability, Deformity, and Disease in the Grimms' Fairy Tales, author Ann Schmiesing analyzes various representations of disability in the tales and also shows how the Grimms' editing (or "prostheticizing") of their tales over seven editions significantly influenced portrayals of disability and related manifestations of physical difference, both in many individual tales and in the collection overall"--Publisher.